PENEGAKAN HUKUM PIDANA LINGKUNGAN TERHADAP PELAKU TINDAK PIDANA PEMBALAKAN LIAR - Erlina B; Okta Ainita; Fissabilla Novita (Fakultas Hukum Universitas Tulang Bawang, 2021)
The main focus of this research is the factors that cause criminal acts, participate in marketing timber from illegal logging and the application of environmental criminal law to the perpetrators of criminal acts and participate in marketing timber from illegal logging. The research method used in this research is juridical normative and empirical. Based on the research results, it was found that the causes of illegal logging in Cikolak Teluk Pandan Village, Pesawaran District, included internal factors including educational factors, personal factors, biological pathogenic factors and pneumonia. External factors include environmental factors, lack of protection, lack of community empowerment, global development factors and economic factors. Enforcement of environmental criminal law against perpetrators of criminal acts by participating in marketing timber from illegal logging, namely imprisonment for 1 (one) year and a fine of Rp. 500,000,000.00 (five hundred million rupiah) provided that if the fine is not paid, it will be replaced by imprisonment for 2 (two) months.